The Competitions, Negotiations, and Collaborations of Regional Integration: A Perspective on Sustainable Management of Water Resources in Pingtung Plain, Taiwan - Tsai, Shuchen; Lee, Suhsin; Zou, Zhe; Chu, Tajen (Sustainability, 2022)
A consultative and cooperative perspective on water management is vital in regional sustainability. However, previous approaches often failed to consider the complex trade-offs involved in water resource allocation. This study explores theoretical perspectives on regional integration as a policy goal through the process of water allocation. The main purpose is to explain new areas created by allocation and regional integration with local-scale cases. The connections between post-structuralism, fragmentation, and heterogeneity are explored with five case studies of groundwater zoning: a Xinyuan buried pipe compensation, a Ligang well closure and power shutdown, a Dachaozhou artificial lake, a Wandan hold back well, and a Meinong anti-deep-water wells. Along with the case studies, secondary literature, interviews, and a field investigation were used. The time span of water conflicts was from 1973 to 2019, and the spatial scope is the groundwater distribution area. The study found that regional integration and dynamic balance are each other’s subject and object, which was empirically verified through the water conflicts in agriculture and the semiconductor industry. Regional integration comes through scaled and flexible methods of operation, and is produced through special market agents and post-structural spaces. In the process, the imbalance caused by conflict must also be adjusted and evolved through cooperation, competition, and negotiation to maintain the dynamic balance. This involves internal treatment of the local government, external integration of the central government, and technological evolution within the organization. Accordingly, several suggestions are proposed that may be helpful for sustainable water resource governance. In summary, this study makes up for the shortcomings of water management patterns constructed by simple spatial overlaying of regional integration. Our findings could effectively enhance negotiations and collaboration in water management for regional sustainability.